2021
DOI: 10.17268/sci.agropecu.2021.001
|View full text |Cite
|
Sign up to set email alerts
|

Causal agent of anthracnose in the pea crop (Pisum sativumL.) in northern of Perú: Symptomatology, isolation and identification, pathogenicity and control

Abstract: Pea (Pisum sativum L.) is an economically important crop and of great demand in the national and international market, due to the considerable number of families that depend on its cultivation, especially in the northern and central highlands of Peru. However, the anthracnose is one of the limiting factors for low productive and causes economic losses. The aim of this study was to describe the symptoms, culturally and morphometrically identify the causal agent and to evaluate under in vitro the efficacy of fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…In addition, we found a disparity in the number of studies conducted in each country and a lack of continuity in the studies. It is worth noting that the studies conducted in Colombia and Ecuador cover a wide range of years, while just one study in Venezuela [48] and one in Peru were conducted recently [51]. For each crop, few studies have been published in each country.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In addition, we found a disparity in the number of studies conducted in each country and a lack of continuity in the studies. It is worth noting that the studies conducted in Colombia and Ecuador cover a wide range of years, while just one study in Venezuela [48] and one in Peru were conducted recently [51]. For each crop, few studies have been published in each country.…”
Section: Discussionmentioning
confidence: 99%
“…Of the 71 studies retrieved from the databases, 35 reported Colletotrichum species in the four countries focused upon in this review. Of these, 21 studies reported species in Colombia [18,[21][22][23][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43], five reported species in Venezuela [44][45][46][47][48], only three reported species in Peru [49][50][51], and six reported species in Ecuador [52][53][54][55][56][57].…”
Section: Geographical Distribution Of Colletotrichum Complexes In Nor...mentioning
confidence: 99%
See 3 more Smart Citations